THE EFFECT OF LEADERSHIP AND ORGANIZATIONAL COMMITMENT IN IMPROVING EMPLOYEE PERFORMANCE AT DEPARTMENT OF ENVIRONMENT AND TRANSPORTATION OF BONDOWOSO REGENCY - Imam Wahyudi; Azrina Husin; Suwignyo Widagdo; Agustin H P (ABM: International Journal of Administration, Business and Management, 2021)
In decision-making, leadership and organizational commitment will have an impact on employee performance. The purpose of this study was to examine and analyze the effect of Leadership and Organizational Commitment on Employee Performance at the Department of Environment and Transportation in Bondowoso Regency partially and simultaneously. The sample in this study was 60 respondents who used the purposive sampling technique. Data analysis used multiple regression tests, hypothesis testing, and coefficient of determination (R2). Based on the results of the study, it was stated that leadership and organizational commitment had an effect on employee performance partially and leadership and organizational commitment had an effect on employee performance simultaneously. The results of this study are used as guidelines in making decisions by the Head of the Office.